Diving boldly into COVID‐19 contaminated wastewater: Eyes at nanotechnology‐assisted solutions - Hussein E. Al‐Hazmi; Agata Kot‐Wasik; Amirhossein Shokrani; Joanna Majtacz; Vahid Vatanpour; Muhammad Tajammal Munir; Sajjad Habibzadeh; Aleksander Hejna; Mahnaz Hasanpour; Abbas Mohammadi; Sepideh Ahmadi; Eder C. Lima; et al. (Wiley, 2023)
Abstract Several studies have been directed to find scalable, swift, accurate, and cost‐effective strategies for detecting, monitoring, and treating coronavirus disease 2019 (COVID‐19). Indeed, the lack of a fast and practical method for detecting the infected regions makes decision‐making challenging to combat the critical pandemic‐struck situations. The probable 'wrong', or rather inadequate, decisions not only have a boomerang effect on the economy but also can lead to an increase in the number of infected individuals, degree of hospitalization, and death counts. Although the current clinical methods are effective, they are costly, time‐consuming, and, more particularly, inadequate because of the virus's mutation patterns. In addition, contamination of biomedical wastes with the COVID‐19 virus is a matter of grave concern. Therefore, there is a perpetual need for novel methodologies to delineate the contaminated regions and determine whether those viruses contaminate the wastewater. Although several review papers have been recently published to discuss those concerns, there is a lack of a comprehensive survey of the detection and treatment of the COVID‐19 virus in aqueous media. Herein, we review techniques available as spreading signifiers for detecting the COVID‐19 virus in water resources and wastewater. We classify and integrate techniques into wastewater, sewage, and sludge detection and monitoring. Treatment of COVID‐19‐contaminated wastewater is discussed by classifying and ranking the methodologies nurtured from nanotechnology, including nanoparticle‐based biosensors used in the detection and nanotechnology‐based filtration systems for the removal of COVID‐19 from wastewater. We also highlight the compilation of the detection methodologies in contaminated aqueous media and provide insight into the challenges associated with treating COVID‐19‐contaminated wastewater. The article concludes that international and robust guidelines for virus/bacteria treatment in wastewater are urgently needed to protect the environment and public health, where nanotechnology plays a key role.